The State-Legal Aspect of Ensuring the National Security of the State - Natalia RAKSHA; Anna BORENSTEIN; Elena POZDNYAKOVA; Yulia VETCHINOVA; Sergey LIKHACHEV; Andrey PASHIN (Communications of International Proceedings, 2021)
The article is devoted to the consideration of problematic aspects of the legal regulation of ensuring the national security of the Russian Federation as one of the areas of law enforcement. It is established that the development and improvement of the legal framework for ensuring the national security of the Russian Federation are a necessary and basic condition for the development of the national security system of the state. It is emphasized that in order to create and maintain the necessary level of security of security facilities, it is necessary to develop a system of legal norms regulating relations in the field of national security; contributing to the definition of the main activities of state authorities and management in this area; determining the formation or transformation of national security bodies and a mechanism for monitoring and supervising their activities. The article uses a number of methods of scientific research, in particular, analysis, synthesis, classification, formal-logical, comparative-legal, historical-legal, etc.
Keywords: The State-Legal Aspect; National Security; Improvement.